2021
DOI: 10.21037/tau-20-1295
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for low-risk kidney cancer: a narrative review of contemporary worldwide practices

Abstract: The management trend of low-risk kidney cancer over the last decade has been from treatment with radical nephrectomy, to use of nephron sparing procedures of partial nephrectomy and ablation, as well as the option of active surveillance (AS). This narrative review aims to summarise the available guidelines related to AS and review the published descriptions of regional practices on the management of low-risk kidney cancer worldwide. A search of PubMed, Google Scholar and Cochrane Library databases for studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…8 Furthermore, several professional urological associations, including the European Association of Urology, American Urological Association, and Canadian Urological Association, have expanded their recommendations for RMBs to include use before or during ablation procedures. 18 We saw a gradual increase in our nonablation patients from 2000-2020, coinciding with national trends. Regardless of increasing acceptance of RMBs, we demonstrated that our overall increase in RMB rates directly coincided with the implementation of Atrium Health's ablation biopsy mandate (Figure 1).…”
Section: Discussionmentioning
confidence: 71%
“…8 Furthermore, several professional urological associations, including the European Association of Urology, American Urological Association, and Canadian Urological Association, have expanded their recommendations for RMBs to include use before or during ablation procedures. 18 We saw a gradual increase in our nonablation patients from 2000-2020, coinciding with national trends. Regardless of increasing acceptance of RMBs, we demonstrated that our overall increase in RMB rates directly coincided with the implementation of Atrium Health's ablation biopsy mandate (Figure 1).…”
Section: Discussionmentioning
confidence: 71%
“…In respect to kidney cancer, Wei Cui and Sullivan presented an overview of current AS practices (9). This narrative demonstrated that AS is being applied worldwide with large similarities for selection criteria and surveillance strategies.…”
mentioning
confidence: 99%